PENGARUH INTEGRITAS DAN OBJEKTIVITAS AUDITOR TERHADAP KUALITAS AUDIT - Natalia Paranoan; Ineltasya; Bertha Beloan; Palalangan, Carolus Askikarno; Beatrix Putri Danduru; Nur Eny (Accounting Profession Journal (APAJI), 2023)
The purpose of this study was to examine the effect of auditor integrity and auditor objectivity on audit quality at the Regional Inspectorate Office of Maros Regency. This research uses quantitative research methods. The data obtained by researchers from primary data in the form of questionnaires which were distributed directly to all functional auditors who function as internal auditors at the Regional Inspectorate Office of Maros Regency, totaling 50 people. The results of the research show that the integrity variable has a negative effect and insignificant effect, while the objectivity variable has a positive effect and significant effect on audit quality.